Molecular Authentication of Radix Behen Albi ("Bahman Sefid") Commercial Products Reveals Widespread Adulteration - Abdolbaset Ghorbani; Mahmoud Mosaddegh; Somayeh Esmaeili*; Hugo De Boer (Iranian Society of Pharmacognosy, 2020)
Background and objectives: The roots of Centaurea behen L., (Asteraceae) known as Radix Behen Albi are used as an aphrodisiac, anti-lithiasis and general tonic. It is available as dried or powdered roots in the herbal markets of Iran. Confirming the identity of this medicinal root using conventional methods is challenging because of lack of the diagnostic characters and market samples are easy to misidentify or adulterate. Methods: This study aimed to authenticate 13 Radix Behen Albisamples purchased from different herbal markets in Iran and to identify the potential adulterants through DNA barcoding. Nuclear (nrITS) and plastid (trnL-F spacer, matK and rbcL) DNA regions were used as barcoding markers. A reference database was compiled using sequences from herbarium voucher specimens and publicly available sequences. Results: Among used barcode regions nrITS was the best marker for species identification followed by trnL-F spacer. MatK and rbcL were able to identify samples to the family level. This study showed that none of the market samples belonged to the authentic Centaurea behen L. Sixty-nine percent of samples were Cousinia spp. (Asteraceae), 23% Korshinskya spp. (Apiaceae) and 8% Crambe spp. (Brassicaceae). This substitution does not only hinder consumers obtain the desired medicinal effects of Radix Behen Albi but also raises concerns about the pharmacovigilance of this medicinal root sold in the markets. Conclusion: The present study shows the need for monitoring and authentication of crude herbal drugs in the markets of Iran, and that DNA barcoding is a suitable tool for this purpose.